An anterior mediastinal cystic lesion pathologically confirmed as a mediastinal pancreatic pseudocyst after thoracoscopic resection: a rare case report and literature review - Kui Zhai; Xingpeng Miao; Guiling Xue; Zhanyu Yuan; Mao Jia; Mingyan Chen; Renzhong Zha (Frontiers in Pediatrics)
BackgroundMediastinal lesions have diverse etiologies, with thymoma, cystic teratoma, and lymphoma being relatively prevalent. In contrast, a pancreatic pseudocyst within the mediastinum is exceedingly rare and can often be mistaken for a thymic cyst or teratoma.Case presentationA 17-year-old female presented with a cough and sputum production. Chest CT revealed an anterior mediastinal mass, initially raising the suspicion of a thymic cyst. Thoracoscopic exploration and resection revealed a cystic lesion with a thick wall and brownish fluid. Both frozen section and final histopathological analysis confirmed a mediastinal cyst. Immunohistochemical markers (SYN positive, CK7 positive) led to a diagnosis of mediastinal pancreatic pseudocyst. The patient experienced significant recovery post-surgery, with a marked improvement in symptoms.ConclusionThis case highlights the importance of including mediastinal pancreatic pseudocyst in the differential diagnosis of anterior mediastinal cystic lesions. A thorough clinical and radiological assessment, along with surgical pathology and immunohistochemical profiling, is essential for accurate diagnosis and appropriate management.